2020
DOI: 10.1177/0890117120905240
|View full text |Cite
|
Sign up to set email alerts
|

Does Adherence to Mediterranean Diet Mediate the Association Between Food Environment and Obesity Among Non-Hispanic Black and White Older US Adults? A Path Analysis

Abstract: Purpose: This study aims to test the hypothesis that in addition to a direct effect of food environment on obesity, food environment is indirectly associated with obesity through consuming Mediterranean diet (MD). Design: Cross-sectional secondary data analysis. Setting: Nationwide community-dwelling residency. Sample: A total of 20 897 non-Hispanic black and white adults aged ≥45 years who participated in the REasons for Geographic and Racial Differences in Stroke study and completed baseline assessment durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Even though MedDiet adherence has previously been assessed in populations living throughout the world [2], including elderly Portuguese [26] and the United States [27][28][29][30][31], few studies have examined MedDiet adherence in communities with immigrants from countries in which the MedDiet is a settled cultural heritage. The current study aimed to assess MedDiet adherence and its associated factors in a Portuguese immigrant community in the Central Valley of California, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Even though MedDiet adherence has previously been assessed in populations living throughout the world [2], including elderly Portuguese [26] and the United States [27][28][29][30][31], few studies have examined MedDiet adherence in communities with immigrants from countries in which the MedDiet is a settled cultural heritage. The current study aimed to assess MedDiet adherence and its associated factors in a Portuguese immigrant community in the Central Valley of California, USA.…”
Section: Introductionmentioning
confidence: 99%
“…The usage of more granular data, such as census tracts, would increase exposure variability compared to county-level analyses of mRFEI scores [67]. Although the mRFEI score is an established measure for the food environment [23,48,68], there may be potential exposure misclassification, as there was no information on the specific food options provided at each food retailer. Furthermore, the binary grouping of establishments into healthy vs. unhealthy may not accurately represent the food environment.…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean diet encourages high consumption of plant-based foods, including fruits, vegetables, olive oil, whole grains, and nuts. Chen et al surveyed more than 20 000 people in 49 states in the US older than 45 years and found that less than half reported high adherence to the Mediterranean diet, and on average, people scored 4.36 of 9 on Mediterranean diet adherence. Having a lower household income was associated with lower adherence to the Mediterranean diet.…”
mentioning
confidence: 86%